1960. Mucosal rAd5 Immunization against SARS-CoV-2 Spike Elicits Cross-Reactive Nasal and Serum Neutralizing Antibodies and Protects Against Beta Variant Challenge in African Green Monkeys. (15th December 2022) - Flitter, Becca A; Tedjakusuma, Sarah N; Lester, Colin A; Neuhaus, Elena D; Johnson, Susan; Dora, Emery G; Peinovich, Nadine; Jegede, Clara B; Tucker, Sean N
Abstract: Background: Mucosal vaccination may offer increased protection against SARS-CoV-2 compared to parental immunization. Here, we describe immunogenicity and efficacy following viral challenge in non-human primates after intranasal delivery of three unique non-replicating adenoviral vector vaccine (rAd5) candidates. Methods: African green monkeys (AMG) were prime boost immunized 29 days apart with vaccine candidates either expressing the parental spike protein alone (Wuhan-S), spike plus nucleocapsid (Wuhan-S-N), or the spike protein from the beta variant (beta-S). Serum and nasal swabs were collected every 14 days and humoral responses to full length spike (S) and receptor binding domain (RBD) were assessed. All AMGs were challenged with SARS-CoV-2 B.1.351 (beta variant) on day 56. Viral loads measured every two days by TCID50 in nasal washes and bronchial lavage fluid post challenge. Results: Mucosal immunization with Wuhan-S induced significant increases in serum IgG and IgA responses against the homologous parental lineage, as well as beta, delta, and omicron variants. In nasal samples, Wuhan-S immunization elicited over 500-fold increases in in cross-reactive IgA against multiple variants of concern including delta and omicron. While the beta-S rAd5 vaccine candidate induced enhanced serum IgG responses to homologous S and RBD proteins, this approach resulted in less cross-reactive antibodies to other variants compared to Wuhan-S rAd5 vaccine. Despite the differences in the ability to elicit cross-reactive antibody responses, all vaccinated AMGs challenged with SARS-CoV-2 B.1.351 (beta variant), had a significant reduction in viral titers by TCID50 in the nasal passages and reduced viral load in bronchial lavage fluid compared to unvaccinated controls. Conclusion: These results demonstrate mucosal administration of rAd5 clinical candidate vaccine, Wuhan-S, is immunogenic and offers cross-protective humoral responses in both serum and nasal compartments against a mismatched SARS-CoV-2 challenge virus. Disclosures: Becca A. Flitter, PhD, MPH, Vaxart Inc: Stocks/Bonds Sarah N. Tedjakusuma, n/a, Vaxart Inc: Stocks/Bonds Colin A. Lester, n/a, Vaxart Inc: Stocks/Bonds Elena D. Neuhaus, n/a, Vaxart Inc: Stocks/Bonds Susan Johnson, PhD, Vaxart Inc: Stocks/Bonds Emery G. Dora, n/a, Vaxart Inc: Stocks/Bonds Nadine Peinovich, MPH, Vaxart Inc: Stocks/Bonds Clara B. Jegede, n/a, Vaxart Inc: Stocks/Bonds Sean N. Tucker, PhD, Vaxart Inc: Stocks/Bonds.